Single cell migration in oral squamous cell carcinoma – possible evidence of epithelial–mesenchymal transition in vivo. (16th April 2015) - Jensen, David H.; Reibel, Jesper; Mackenzie, Ian C.; Dabelsteen, Erik
<x xml:space="preserve">Abstract</x> Background The invasion of cancer cells into the surrounding normal tissue is one of the defining features of cancer. While the phenomena of tumour budding, epithelial–mesenchymal transition and the presence of myofibroblasts have independently been shown to be related to a poor prognosis of oral carcinomas, their relationship has not been examined in detail. Methods Paraffin‐embedded tissues from 28 patients with oral squamous cell carcinomas were stained with antibodies to cytokeratin, α‐SMA, vimentin, E‐cadherin, N‐cadherin and Twist and evaluated for their expression in relation to invasive cancer cells and the surrounding tumour stroma. Results and conclusions A direct, histological relationship between invading, budding tumour cells and myofibroblasts was occasionally seen but was not a general feature. Most of the budding tumour cells at the invasive front had a decreased expression of E‐cadherin, but we did not find that this was associated with a consistent or clear increase in either N‐cadherin or vimentin. We therefore suggest that the budding of tumour cells is not dependent upon either myofibroblasts or a complete epithelial–mesenchymal transition and that these phenomena most likely represent separate processes in tumour progression.